2018
DOI: 10.1017/s1049023x18000080
|View full text |Cite
|
Sign up to set email alerts
|

Is Distance to the Nearest Registered Public Automated Defibrillator Associated with the Probability of Bystander Shock for Victims of Out-of-Hospital Cardiac Arrest?

Abstract: For out-of-home cardiac arrests, proximity to a PAED was associated with bystander shock in the greater Montreal area. Strategies aiming to increase accessibility and use of these life-saving devices could further expand this advantage by assisting bystanders in rapidly locating nearby PAEDs. Neves Briard J , de Montigny L , Ross D , de Champlain F , Segal E . Is distance to the nearest registered public automated defibrillator associated with the probability of bystander shock for victims of out-of-hospital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Applications of this type alone are not novelties [18]. However, their use in practice and their use as a potential tool for faster location of a device that can be used to perform quick de brillation have only recently become a topic of research [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Applications of this type alone are not novelties [18]. However, their use in practice and their use as a potential tool for faster location of a device that can be used to perform quick de brillation have only recently become a topic of research [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Neither the international nor the national variation is fully understood but may be attributed to multiple factors such as organization of the Emergency Medical Service (EMS) system, 16,17 the response time of the EMS, 16 bystander cardiopulmonary resuscitation (CPR), 4,18 and the use of Automatic External Defibrillators 4,16,19,20 . However, Dyson et al 21 found that the Utstein core factors accounted for only 51% of the global variation in survival to hospital discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, defibrillation can be performed by bystanders if an automatic external defibrillator (AED) is available. Any OHCA taking place within a 100 m radius of an AED is considered to be "covered", as the device is reachable within 90 seconds by brisk walking, allowing defibrillation to be performed within 3-5 minutes [4][5][6][7], as recommended by the American Heart Association (AHA) [8]. Therefore, public authorities have launched public access defibrillation (PAD) programs, as recommended by the European Resuscitation Council Guidelines [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the use of an AED by a bystander remains low for a number of reasons. AEDs may be misplaced regarding location of OHCAs [4][5][6][10][11][12], be inaccessible at the time of the OHCA [13][14][15][16] or not registered through the dispatch centre, or bystanders may have difficulty finding them because their locations are poorly indicated [17]. Finally, most OHCAs occur at home, often with no one else around, or with only a sole elderly witness, and these locations are less covered by AEDS [18].…”
Section: Introductionmentioning
confidence: 99%